Relationship of Complications During Pregnancy and Low Birth Weight in Indonesia: An Ecological Study - Leonny Charisso; Hario Megatsari; AgungDwi Laksono; Mursyidul Ibad (Indian Journal of Forensic Medicine & Toxicology, 2021)
Low birth weight is classified as one of the children’s health problems in Indonesia. Theauthorsconducted astudy to analyze the environmental factors associated with Indonesia’s low birth weight. Thestudy conductedan ecological analysis using secondary data from the Ministry of Health of the Republic of Indonesia report in2018. The study takes all provinces in Indonesia as samples.Besidesthe proportion of low birth weight, therewere 3 other variables analyzed, the proportion of hypertension in pregnancy, the proportion of birth canalbleeding, and the proportion of amniotic fluid discharge. Data were analyzed using cross-tabulation.Theresults show that all three variables tend to affect the proportion of low birth weight and the previous studies.The study concluded that the three independent variables analyzed tend to correlate with the proportion oflow birth weight in Indonesia.